Ultrastructure of Granulosa Cells of Bovine Ovarian Antral Follicles in Relation to Atresia - Pivko J. (Folia Veterinaria, 2020)
The aim of this study was to describe the most common forms of ovarian follicle atresia in large antral follicles of cows and quantify the occurrence of different cell structures in each form. Atresia of antral follicles in ovaries was determined on the basis of ultrastructural images acquired by electron microscopy of ultrathin sections contrasted with uranyl acetate and lead citrate to visualize cell organelles. All forms of atresia in large follicles are accompanied by regressive changes of the granulosa cells. The initial form of atresia is characterized by enlarged intercellular spaces after the disruption of the gap junctions and desmosomes. Small collapsed cells with pyknotic nuclei, substantially reduced the cytoplasm and a higher incidence of lysosomes are located on the surface of the granulosa layer. The stratum granulosum wall collapses and the basal membrane is swollen with a rupture of the lamina basalis. Obliterative atresia is characterized by a multiplied loose connective tissue consisting of collagen fibers, fibroblasts, histiocytes, blood capillaries and sporadically granulocytes. The cystic form of atresia is characterized by small collapsed, pyknotic granulosa cells settled in one or two layers. In luteinization-associated atresia, granulosa cells are hypertrophied, their cytoplasm contains smooth endoplasmic reticulum and mitochondria with tubules. In conclusion, the initial atresia of large antral ovarian follicles is associated with processes of cell death, followed by multiplication of the loose connective tissue cells, its dystrophy and hyalinization of the collagen fibers. Ultrastructural examination could be used as a complementary method to improve histopathological diagnostics of cow reproductive organs in veterinary practice.